Offshore Sea Life ID Guide : East Coast - Howell, Steve N. G.; Sullivan, Brian L., 1971- (Princeton field guides., 2015)
Two-thirds of our planet lies out of sight of land, just offshore beyond the horizon. What wildlife might you see out there? This handy guide, designed for quick use on day trips off the East Coast, helps you put a name to what you find, from whales and dolphins to shearwaters, turtles, and even flying fish. Carefully crafted color plates show species as they typically appear at sea, and expert text highlights identification features. Essential for anyone heading out on a whale-watching or birding trip, this guidebook provides a handy gateway to the wonders of the ocean.